Molecular Techniques for Identification of Species of the Mycobacterium tuberculosis Complex: The use of Multiplex PCR and an Adapted HPLC Method for Identification of Mycobacterium bovis and Diagnosis of Bovine Tuberculosis - Figueiredo, Eduardo Eustáquio de Souza; Júnior, Carlos Adam Conte; Furlanetto, Leone Vinícius; Silva, Flávia Galindo Silvestre; Duarte, Rafael Silva; Silva, Joab Trajano; Lilenbaum, Walter; Paschoalin, Vânia Margaret Flosi (IntechOpen, 2012)
None